Pendampingan Distribusi Pengelolaan Dana Zakat Pada BAZNAS Kota Blitar Melalui Program Blitar Peduli - Fitria, Ida; Setyowati, Eka yuli; Camila, Naila Zulfa Safitri Sofa; Sulistiani, Deti (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This community service activity program aims to assist BAZNAS Blitar City in managing and distributing zakat funds through the Blitar Cares Program. The method used in this community service activity is assistance in distribution and field surveys regarding people who apply for assistance from BAZNAS. The implementation of assistance at BASNAS City of Blitar has the main focus on assisting the management and distribution of zakat funds. Based on the community service activities carried out, it shows that with management and distribution assistance in accordance with Islamic law, zakat funds are more productive and their distribution is right on target, especially for mustahiq who are around the BAZNAS area of Blitar City. The distribution and management of zakat funds at BAZNAS in Blitar City have been carried out properly and effectively, as can be seen from the distribution of food packages every month for the poor and financial assistance for the renovation of residents' houses that are no longer livable, even in supporting the distribution of funds so that BAZNAS does not misuse supervision efforts for recipients of zakat funds, both direct and indirect supervision.